Mulberry anthocyanin biotransformation by intestinal probiotics. (15th December 2016) - Cheng, Jing-Rong; Liu, Xue-Ming; Chen, Zhi-Yi; Zhang, You-Sheng; Zhang, Ye-Hui
Highlights: Mulberry anthocyanin bioconversions by five intestinal bacteria were compared. S. thermophiles and L. plantarum showed great anthocyanin bioconversion potential. Bioavailable metabolites were detected during mulberry anthocyanin bioconversion. Abstract: This study was designed to evaluate mulberry anthocyanins bioconversion traits for intestinal probiotics. Five intestinal beneficial bacteria were incubated with mulberry anthocyanins under anaerobic conditions at 37 °C, and bacterial β-glucosidase activity and anthocyanin level were determined. Results demonstrated that all strains could convert mulberry anthocyanins to some extent. With high β-glucosidase production capacity, Streptococcus thermophiles GIM 1.321 and Lactobacillus plantarum GIM 1.35 degraded mulberry anthocyanins by 46.17% and 43.62%, respectively. Mulberry anthocyanins were mainly biotransformed to chlorogenic acid, crypto-chlorogenic acid, caffeic acid, and ferulic acid during the anaerobic process. Non-enzymatic deglycosylation of anthocyanins also occurred and approximately 19.42% of the anthocyanins were degraded within 48 h by this method.